Bridging the watershed–urban disconnect: a mixed-methods analysis of flood-risk perception and preparedness in Sindh, Pakistan - Suyuhan, Wang; Khoso, Abdul Rasool (Frontiers in Environmental Science, 2026)
IntroductionExtreme flooding events are increasing in frequency due to climate change and posing major challenges for developing countries, where a clear disconnect exists between how floods develop at the watershed level and how communities perceive the risks they face. Thus, this study examines the disconnect between watershed-scale flood generation and community-scale risk perception and preparedness in Sindh, Pakistan.MethodologyThis research employed a mixed-method approach, containing 400 questionnaires as a survey using a 10-point Likert scale for quantitative analysis and 8 in-depth interviews for qualitative data. SPSS was used for statistical analysis, while NVIVO was used for thematic analysis.ResultsThe findings revealed that education level significantly influenced causal attribution of floods (χ2 = 35.82, p <0.001). Only 6.7% of respondents with no formal education implicated watershed-scale causes, compared to 56.7% of those with a bachelor’s degree. Hierarchical regression analysis identified watershed awareness, self-efficacy, and trust in institutions as key predictors of preparedness, explaining 41% of the variance (R2 = 0.41). Self-efficacy partially mediated the link between watershed perception and preparedness [indirect effect β = 0.08, 95% CI (0.041, 0.129)]. Thematic analysis of qualitative data identified inadequate local infrastructure as a primary community concern, with repeated flood losses exacerbating psychological vulnerability.ConclusionThe study concludes that respondents with lower education levels primarily perceived floods as locally caused, indicating perceived deficiencies in infrastructure, whereas respondents with higher education emphasized watershed-scale causes. Governmental failure was also perceived as a major contributing factor to flooding. The study recommends tailored risk communication, enhanced watershed education, and transparent governance to enhance flood resilience.